2017
DOI: 10.1111/tmi.12901
|View full text |Cite
|
Sign up to set email alerts
|

Non‐communicable diseases and HIV care and treatment: models of integrated service delivery

Abstract: Abstractobjectives Non-communicable diseases (NCD) are a growing cause of morbidity in low-income countries including in people living with human immunodeficiency virus (HIV). Integration of NCD and HIV services can build upon experience with chronic care models from HIV programmes. We describe models of NCD and HIV integration, challenges and lessons learned.methods A literature review of published articles on integrated NCD and HIV programs in lowincome countries and key informant interviews were conducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
159
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(165 citation statements)
references
References 32 publications
4
159
2
Order By: Relevance
“…We found that older patients (50 years and above) who had well-controlled sugar levels or blood pressure and were also stable on ART were still required to make monthly clinic visits regardless of the DSD provision of 3-monthly visits. This calls for the integrated management of HIV and other co-morbidities that is becoming increasingly important priority due to ageing cohorts of clients and the need to revisit treatment guidelines even in non-HIV services [42][43][44].…”
Section: Study Implications For Countries With Similar Setting As Ugandamentioning
confidence: 99%
“…We found that older patients (50 years and above) who had well-controlled sugar levels or blood pressure and were also stable on ART were still required to make monthly clinic visits regardless of the DSD provision of 3-monthly visits. This calls for the integrated management of HIV and other co-morbidities that is becoming increasingly important priority due to ageing cohorts of clients and the need to revisit treatment guidelines even in non-HIV services [42][43][44].…”
Section: Study Implications For Countries With Similar Setting As Ugandamentioning
confidence: 99%
“…We found that older patients (50 years and above) who had well-controlled sugar levels or blood pressure and were also stable on ART were still required to make monthly clinic visits regardless of the DSD provision of 3-monthly visits. This calls for the integrated management of HIV and other comorbidities that is becoming increasingly important priority due to ageing cohorts of clients and the need to revisit treatment guidelines even in non-HIV services [36], [37], [45].…”
Section: Study Implications For Countries With Similar Setting As Ugandamentioning
confidence: 99%
“…Despite being an infectious disease, care for HIV has evolved into a chronic care model, that involves patient follow-up, continuity of care, monitoring and auxiliary services to maintain patients' health and quality of life. HIV/AIDS prevention and treatment services have been successfully integrated with services focused on maternal and child health, TB, nutritional advice, family planning services, lifestyle advice services and screening programmes for NCDs [21][22][23], and has established strong health systems, financing and infrastructure across many LMIC settings.…”
Section: Hiv As An Example Of Integrated Carementioning
confidence: 99%